Glass powder and conductive copper paste for MLCC (multilayer ceramic capacitor) and preparation method of glass powder and conductive copper paste

Through the use of Zn-Bi-free lead-free glass powder formula and inorganic powder additives, the problem of easy crystallization and sintering stress of glass powder is solved, the resistance and conductivity of the plating solution of copper slurry is improved, and the reliability of MLCC is enhanced. and solder resistance.

CN119118523AActive Publication Date: 2024-12-13EAST CHINA UNIV OF SCI & TECH

Patent Information

Application Number
CN202411281286.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-13
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing glass powders are easy to crystallize, phase separation, and high temperatures in MLCC, resulting in an increase in interfacial stress, affecting the resistance and conductivity of the electroplating solution of copper slurry, and excessive temperature gradient changes during copper slurry during sintering, causing stress problems.

Method used

Using Zn-Bi-free lead-free glass powder formula, containing SiO2, B2O3, BaO, CaO, TiO2, CuO, Sb2O3 and NaF, the melting temperature and high temperature viscosity are reduced by excessive alkali and alkaline earth metals, and the density and acid resistance of the glass are increased. and add inorganic powder additives such as lithium cylindrical powder to match the expansion coefficient of copper powder and ceramic substrates, optimize the copper slurry formula to reduce sintering stress.

Benefits of technology

Improves the wetting and thermal expansion matching of glass powder, enhances the resistance and conductivity of the electroplating solution of copper slurry, reduces sintering stress, forms dense and acid-resistant copper electrodes, and improves the reliability and welding resistance of MLCC. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005041698090000091
    Figure BDA0005041698090000091
  • Figure BDA0005041698090000092
    Figure BDA0005041698090000092
  • Figure BDA0005041698090000101
    Figure BDA0005041698090000101
Patent Text Reader

Abstract

The invention discloses glass powder and conductive copper paste for an MLCC (multilayer ceramic capacitor) and a preparation method of the glass powder and the conductive copper paste. The formula of the glass powder comprises 18.0% to 28.0% of SiO2, 25.0% to 35.0% of B2O3, 30.0% to 45.0% of BaO, 0% to 10% of CaO, 0% to 5% of Na2O, 0% to 8.0% of TiO2, 0% to 6% of CuO, 0% to 5.0% of Sb2O3 and 0% to 5.0% of NaF. Basic components of the glass powder do not contain Bi and Zn, a system is SiO2-B2O3-Na2O-BaO, TiO2, CuO, Sb2O3, NaF and the like are added into the basic glass components, Sb2O3 can reduce the surface tension of the glass and improve the wettability between the glass and the copper powder and ceramic, and TiO2 and CuO enhance the acid resistance of the glass and increase the compactness of an interface. NaF is used as a glass liquid clarifying agent, so that the clarifying speed of the glass liquid can be increased, the high-temperature viscosity of the glass powder can be reduced, the flowability of the glass powder is enhanced, and the interface densification speed is increased. The average particle size of the glass powder is 1.8-2.5 microns, and the thermal expansion coefficient of the glass is 6.5-9.5 ppm / DEG C. The glass powder has an obvious sintering assisting effect on the copper paste, after the copper paste is applied to an MLCC ceramic substrate to be sintered, the copper paste and the ceramic substrate have firm physical and chemical bonding, and the MLCC shows excellent electrical properties, adhesive force and good electroplating liquid resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electronic components, and in particular relates to a glass powder and a conductive copper paste for MLCC and a preparation method thereof. Background Art

[0002] In recent years, with the rapid development of the electronic information industry, electronic components are moving towards high reliability, miniaturization, integration and low cost. The performance requirements for materials are becoming increasingly higher and the demand is growing year by year.

[0003] Compared with precious metal paste, conductive copper paste is cheaper, and its conductivity, ductility, and solderability are close to those of precious metal paste. It is widely used in electronic industries such as MLCC and LTCC. However, copper paste still has poor adhesion, which easily leads to electrode peeling and corrosion resistance of electroplating solution. Glass powder, as a key component of copper paste, plays an important role in the adhesion, bonding strength, sintering density, etc. of copper paste. Glass powder for copper paste is developing in the direction of lead-free and non-toxic. US2014 / 0363681A1 discloses a thick layer printed copper conductive paste suitable for aluminum nitride (AlN) substrate. The glass powder used in the copper paste is 45-65% Bi2O3, 25-45% SiO2, and 1-15% B2O3. When applied to aluminum nitride substrates, the thermal expansion coefficient is well matched and excellent adhesion is shown. However, bismuth glass melt is easy to phase separate and has poor acid resistance and electroplating solution resistance, which can easily affect the long-term reliability of the product. CN116535097A discloses a zinc borosilicate glass system for multilayer ceramic capacitors (MLCC) having a base component and external components of CuO, TiO2 and ZrO2 in a mass ratio of 100:(0.5-1.5):(0.5-1.5):(0.5-1.5). The glass powder of the invention has a lower softening point, which helps to densify the copper paste at low temperature and improve the electrode's resistance to electroplating liquid. The glass powder has good wettability at high temperature, thereby enhancing the adhesion of the copper paste. However, when the glass powder is co-fired, ZnB2O4 crystals are easily precipitated, which increases the stress at the substrate interface and reduces the wettability of the glass powder, thereby reducing the reliability of the product.

[0004] Therefore, it is necessary to design a Zn-free, Bi-free, lead-free glass. The glass powder used in the copper paste should have good resistance to electroplating liquid, not produce products that increase stress with the ceramic substrate, have high thermal expansion matching with the ceramic substrate and copper powder, and have a significant sintering effect on the copper paste. In addition, in order to solve the problem of stress caused by excessive temperature gradient changes during the sintering and cooling process of the copper paste, the copper paste components can be optimized. Summary of the invention

[0005] In view of the problems in the above background technology, the present invention provides a glass powder for MLCC, a conductive copper paste and a preparation method thereof, which solves the problems of easy crystallization, phase separation and high temperature volatility in the glass powder of the prior art, reduces the stress caused by the growth or transformation of the crystal form of the interface product, improves the wettability and thermal expansion matching of the glass powder to the copper powder and the ceramic substrate, thereby enhancing the electroplating liquid resistance and copper paste conductivity of the copper paste. At the same time, by optimizing the copper paste formula method, the problem of stress generated at the MLCC copper paste interface due to the excessive cooling gradient of the MLCC is solved.

[0006] To achieve the above object, the technical solution adopted by the present invention is:

[0007] In a first aspect, the present invention provides a Zn-free, Bi-free, lead-free glass powder: 18.0-28.0% SiO2, 25.0-35.0% B2O3, 30.0-45.0% BaO, 0-10% CaO, 0-5% Na2O, 0-8.0% TiO2, 0-6% CuO, 0-5.0% Sb2O3, 0-5.0% NaF. The glass formers SiO2 and B2O3 serve as the skeleton of the glass powder, and excessive alkali (Na2O) and alkaline earth metals (CaO, BaO) are added to reduce the glass melting temperature and high temperature viscosity, while promoting B2O3 to form a more compact structure [4]. - TiO2, CuO, and Sb2O3 can reduce the surface tension of glass, enhance the acid resistance of glass, and increase the density of the interface. NaF, as a glass clarifier, can speed up the clarification of glass and reduce the high-temperature viscosity of glass powder.

[0008] As a preferred embodiment of the first aspect of the present invention, the glass preferably comprises 24.0-26.0% SiO2, 25.0-29.0% B2O3, 30.0-40.0% BaO, 2-7% CaO, 0-5% Na2O, 0-4.0% TiO2, 0-5% CuO, 0-5.0% Sb2O3, and 0-5.0% NaF. Among them, (Sb2O3+NaF)≥2.0%, and (Na2O+CaO+BaO)≥40%. Glass within this element range has good glass forming properties, good sintering activity, good acid resistance, and good adhesion to the substrate.

[0009] In the second aspect, the present invention provides a conductive paste for MLCC, which is prepared by mixing 65.0-80.0% copper powder, 7.0-15.0% glass powder, 15.0-23.0% organic carrier, 0-5.0% inorganic powder additive, etc., calculated by mass percentage. The inorganic powder additive is selected from powders with extremely small expansion coefficients or negative expansion, such as eucryptite powder, to solve the problem of stress generated at the interface of MLCC copper paste due to excessive MLCC cooling gradient.

[0010] As a preferred embodiment of the second aspect of the present invention, the solid content of the slurry (glass powder + copper powder) is ≥ 80%, thereby increasing the dry film density of the slurry and increasing the edge thickness of the MLCC terminal electrode.

[0011] As a preferred embodiment of the second aspect of the present invention, the organic carrier comprises 70-80% of solvent and 20-30% of resin by mass percentage. The preferred solvent comprises two of diethylene glycol butyl ether acetate, dipropylene glycol butyl ether, and terpineol; the resin is preferably acrylic resin, and two of the molecular weights are 25W to 50W.

[0012] In a third aspect, the present invention further discloses a method for preparing a conductive copper paste, comprising the following steps:

[0013] S1. Weigh the solvent and the resin, dissolve the resin uniformly in the solvent at 80-90° C., and stir thoroughly to form a uniform organic carrier.

[0014] S2, weigh glass powder, copper powder, and the organic carrier and inorganic powder additive prepared in step S21 according to a certain proportion, and stir them in turn using a high-speed homogenizer to form a uniform slurry. Then, the slurry is fully ground using a three-roll mill to finally prepare a copper conductive slurry that meets the performance requirements.

[0015] Furthermore, in step S2, the preparation of the glass powder includes the following steps:

[0016] S21. Weigh glass raw materials, mix and grind them thoroughly, put them into a platinum crucible, and melt them at 1200° C. for 60 minutes. Then pour the molten glass into deionized water for quenching, so that the glass is broken into particles.

[0017] S22, coarsely grinding and finely grinding the glass powder prepared in step S21 by ball milling, and reducing the particle size D50 of the glass powder after ball milling to 2-3 μm.

[0018] As a preferred embodiment of the third aspect of the present invention, the carrier A and carrier B prepared by S1 are both filtered through a 200-400 mesh filter, the slurry prepared by S2 is filtered through a 200-300 mesh filter, the glass powder is coarsely ground through a 100-200 mesh screen, and then finely ground and dried and filtered through a 200-400 mesh screen.

[0019] As described above, the copper conductive paste is attached to the end surface of MLCC of size 0402 and above, and then dried and sintered in sequence to obtain a copper electrode. The drying temperature is 120-130°C and the time is 10-20 minutes; the sintering process is: first, in a wet nitrogen atmosphere, the temperature is increased to 500°C at a heating rate of 20-50°C / min and then kept at this temperature for 10 minutes, and then in a dry nitrogen atmosphere, the temperature is increased to 650-750°C at a heating rate of 30-50°C / min and then kept at this temperature for 10 minutes.

[0020] In the application described above, the copper terminal electrode is composed of a copper film and a substrate, and there is no bulging, cracking, or glass overflow on the end surface. The average square resistance of the copper film is 4.5-15.3 mΩ / square, and the tensile force of the terminal electrode is 10-15 LB.

[0021] Principle of the invention: The glass powder added to the conductive paste for LTCC of the present invention can help reduce the wetting angle between copper powder and MLCC substrate, improve the acid resistance of the paste after sintering, and control the thermal expansion coefficient of the copper paste. At the same time, it can effectively reduce the liquefaction temperature of copper powder, promote the densification process of the paste during sintering, reduce sintering time, and reduce energy consumption. First, the Sb2O3 in the glass powder can reduce the surface tension of the glass, enhance the acid resistance of the glass and increase the density at the interface. NaF reacts with Si to form Si-O-Na non-bridging oxygen connection with SiF, reduce the viscosity of the glass powder and clarify the glass liquid, which can speed up the clarification speed of the glass liquid and reduce the high temperature viscosity of the glass powder. Secondly, the glass powder does not contain Bi, Zn, Pb and other components that are easy to crystallize, separate into phases, and are volatile at high temperatures. The addition of TiO2 and CuO can improve the wettability and thermal expansion matching of the glass powder to the copper powder and ceramic substrate, forming the connection interface of Cu-glass powder-Cu-nickel and Cu-glass-substrate, thereby enhancing the electroplating liquid resistance and conductivity of the copper paste and improving the end pulling force of the MLCC.

[0022] Inorganic powder additives can inhibit the shrinkage of copper powder during sintering, and can effectively avoid the warping and cracking of MLCC substrates caused by different shrinkage starting temperatures during the sintering of copper paste and MLCC substrates. The specific principle is: the microscopic essence of the shrinkage of copper powder during sintering is that the centers of two particles are close to each other, fused into a large particle, and the grains grow. The inorganic powder blocks the contact between the two particles, and the grain growth process slows down. In addition, inorganic powder additives can soften to form a liquid phase, wet the copper powder and the MLCC substrate, so that the sintered copper film and the LTCC substrate have good bonding.

[0023] The copper paste prepared in the present invention can be sintered with the MLCC substrate to form a dense terminal electrode, and has a strong bonding force with the MLCC substrate. The MLCC device prepared in combination with the present invention has the advantages of high sintering densification and high electroplating pass rate, and the internal stress distribution of the chip device after sintering is uniform and moderate, the square resistance is small, and the solder resistance is strong. The pass rate of reliability tests such as heating aging and accelerated life is high.

[0024] Compared with the prior art, the gain effects of the present invention include:

[0025] The glass powder prepared by the present invention is non-toxic and environmentally friendly and has excellent chemical stability and thermal stability. The glass has a high matching degree of thermal expansion coefficient, the wettability between glass and copper powder is good, and the glass powder has an obvious sintering-aiding effect. The conductive copper paste formed by mixing the glass powder, copper powder, organic carrier, and inorganic powder is combined with the MLCC electrode sintering preparation process of the present invention to prepare a copper-terminal paste electrode with excellent comprehensive performance, high sintering densification, low porosity, and good conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 (a) to (i) are end surface SEM images of Examples 1 to 6 and Comparative Examples 1 to 3 of the present invention.

[0028] Figure 2 (a) to (f) are cross-sectional SEM images of Examples 1 to 4 and Comparative Examples 2 to 3 of the present invention. DETAILED DESCRIPTION

[0029] In order to more clearly illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. The described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, other embodiments obtained by ordinary technicians in the field without making creative work all belong to the scope of protection of this application.

[0030] The present invention is described below in conjunction with specific embodiments.

[0031] Example 1

[0032] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0033] The organic carrier of this embodiment includes carrier A and carrier B. Carrier A includes the following components by weight: 50% terpineol, 10% diethylene glycol butyl ether acetate, and 30% acrylic resin. Carrier B is 40%, 40% diethylene glycol butyl ether acetate, and 20% acrylic resin. And carrier A:carrier B=3:2.

[0034] The copper powder in this embodiment includes spherical copper powder with D50=5 μm and hexagonal copper powder with D50=1.5 μm, and the mass ratio of the two is 1:2.

[0035] The glass powder described in this embodiment includes the following components in weight percentage: 26.0% SiO2, 25.0% B2O3, 30.0% BaO, 7.0% CaO, 5.0% Na2O, 2.0% TiO2, 2.0% CuO, 1.0% Sb2O3, and 2.0% NaF.

[0036] The method for preparing the terminal electrode copper slurry described in this embodiment comprises the following steps:

[0037] S1. Weigh the solvent and the resin, dissolve the resin uniformly in the solvent at 80-90° C., and form a uniform organic carrier by fully stirring.

[0038] S2, weigh the organic carrier A, carrier B, glass powder, copper powder A and copper powder B prepared in step S1 according to proportion and stir them evenly to form a slurry. Then, grind the slurry fully with a three-roll mill to finally prepare a copper slurry that meets the performance requirements.

[0039] The method for preparing the glass described in this embodiment comprises the following steps:

[0040] S1. Weigh the glass raw materials, mix and grind them thoroughly, and then put them into a platinum crucible. Melt them at 1300℃ for 1.5h.

[0041] S2. Pour the molten glass into deionized water for quenching, and crush the molten glass with a ball mill to reduce the particle size D50 of the particles to 2 μm, thereby obtaining the glass powder.

[0042] Use and testing method of copper paste described in this embodiment

[0043] The copper paste is applied to the MLCC terminal substrate by dip coating to form a 50-60 μm thick paste. The drying temperature is 120-130°C for 10-20 minutes. Then, the temperature is raised to 500°C at a heating rate of 20-50°C / min in a wet nitrogen atmosphere and then kept at this temperature for 10 minutes. Then, the temperature is raised to 650-750°C at a heating rate of 30-50°C / min in a dry nitrogen atmosphere and then kept at this temperature for 10 minutes.

[0044] The acid and alkali resistance test conditions of the glass powder are 55°C, the immersion time is 60 minutes, the pH of the acid solution is 2, and the pH of the alkali solution is 10. After immersion, cleaning and drying, the glass powder is weighed to compare the quality changes before and after soaking in acid and alkali solutions.

[0045] The viscosity test instrument, rotor model and test conditions of the copper slurry are: Brookfield@Spindle No.SC-14 / 6R at 25°C, and the viscosity change is detected at 10 rpm.

[0046] The electrical properties of the copper film are measured by a four-probe resistance meter. In the present invention, square resistance refers to the resistance between two opposite sides of a square thin film conductive material.

[0047] The film thickness and edge film thickness were tested using the DPA analysis method under SEM @ 500 times.

[0048] The bonding strength between the terminal electrode and the ceramic substrate is characterized by the magnitude of the tensile force. First, the terminal paste is capped on the 0805 MLCC and sintered according to the copper terminal paste sintering process. After the terminal electrode is sintered, the copper film is tin-plated and nickel-plated, and then the tin wire is welded for tensile testing.

[0049] The acid and alkali resistance results, hemispherical temperature and transition temperature of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 1 is less than 0.2%. The viscosity change of the copper paste in Example 1 after one month of storage is shown in Table 2, and the change rate is less than 5%. The bonding layer with the end face of MLCC is shown in Table 2. Figure 1 , the porosity of the interface is less than 5%, the edge thickness is 5μm, the resistance is 5mΩ / square, and the tension of the end is 12LB.

[0050] Example 2

[0051] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.

[0052] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0053] The glass powder described in this embodiment includes the following components in weight percentage: 25.0% SiO2, 25.0% B2O3, 36.0% BaO, 4.0% CaO, 1.0% Na2O, 7.0% TiO2, 0% CuO, 1.0% Sb2O3, and 1.0% NaF.

[0054] The acid and alkali resistance results, hemispherical temperature and transition temperature of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 2 is less than 0.2%. The viscosity change of the copper paste in Example 2 after one month of storage is shown in Table 2, and the change rate is less than 5%. The bonding layer with the end face of MLCC is shown in Table 2. Figure 1 , the interface porosity is less than 5%, the edge thickness is 4.5μm, the resistance is 7mΩ / square, and the tension at the end is 10LB.

[0055] Example 3

[0056] Except for the glass formula and the glass ratio in the slurry of this embodiment being different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.

[0057] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0058] The glass powder described in this embodiment includes the following components in weight percentage: 25.0% SiO2, 25.0% B2O3, 38.0% BaO, 2.0% CaO, 3.0% Na2O, 0.0% TiO2, 5.0% CuO, 1.0% Sb2O3, and 1.0% NaF.

[0059] The acid and alkali resistance results, hemispherical temperature and transition temperature of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 3 is less than 0.2%. The viscosity change of the copper paste in Example 3 after one month of storage is shown in Table 2, and the change rate is less than 2.0%. The bonding layer with the end face of MLCC is shown in Table 2. Figure 1 , the interface porosity is less than 5%, the edge thickness is 4.3μm, the resistance is 5mΩ / square, and the tension at the end is 9LB.

[0060] Example 4

[0061] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.

[0062] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0063] The glass powder of this embodiment includes the following components in weight percentage: 24.0% SiO2, 29.0% B2O3, 35.0%BaO, 2.0%CaO, 2.0%Na2O, 3.0%TiO2, 3.0%CuO, 1.0%Sb2O3, 1.0%NaF.

[0064] The acid and alkali resistance results of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 4 is less than 0.2%. The viscosity change of the copper paste in Example 4 after one month of storage is shown in Table 2, and the change rate is less than 2.0%. The bonding layer with the end face of MLCC is as shown in Table 2. Figure 1 , the interface porosity is less than 5%, the edge thickness is 4.5μm, the resistance is 11mΩ / square, and the tensile force at the end is 9LB.

[0065] Example 5

[0066] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.

[0067] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0068] The glass powder described in this embodiment includes the following components in weight percentage: 24.0% SiO2, 26.0% B2O3, 40.0% BaO, 2.0% CaO, 1.0% Na2O, 1.0% TiO2, 4.0% CuO, 1.0% Sb2O3, and 1.0% NaF.

[0069] The acid and alkali resistance results of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 5 is less than 0.2%. The viscosity change of the copper paste in Example 5 after one month of storage is shown in Table 2, and the change rate is less than 2.0%. The bonding layer with the end face of MLCC is as shown in Table 2. Figure 1 , the interface porosity is less than 5%, the edge thickness is 5.0μm, the resistance is 13mΩ / square, and the tension at the end is 8LB.

[0070] Example 6

[0071] Except for the glass formula and the glass ratio in the slurry of this embodiment which are different from those of Embodiment 1, the other slurry processing methods, sintering processes and testing methods are exactly the same.

[0072] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0073] The glass powder described in this embodiment includes the following components in weight percentage: 25.0% SiO2, 25.0% B2O3, 38.0% BaO, 2.0% CaO, 3.0% Na2O, 0.0% TiO2, 5.0% CuO, 1.0% Sb2O3, and 1.0% NaF.

[0074] The acid and alkali resistance results of the glass powder in this embodiment are shown in Table 1. The acid and alkali resistance weight loss rate of the glass powder in Example 4 is less than 0.2%. The viscosity change of the copper paste in Example 4 after one month of storage is shown in Table 2, and the change rate is less than 2.0%. The bonding layer with the end face of MLCC is as shown in Table 2. Figure 1 , the interface porosity is less than 5%, the edge thickness is 5.2μm, the resistance is 9mΩ / square, and the tension at the end is 12LB.

[0075] Example 7

[0076] Except for the difference in the glass ratio in the slurry of this embodiment from that of Embodiment 1, the other glass formulas, slurry processing methods, sintering processes and testing methods are exactly the same.

[0077] The slurry described in this embodiment contains 71% copper powder, 12% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0078] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is less than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1 , the interface porosity is less than 5%, the edge thickness is 5.2μm, the resistance is 15mΩ / square, and the tensile force at the end is 14LB.

[0079] Example 8

[0080] Except that the ratio of glass to copper powder in the slurry of this embodiment is different from that of Embodiment 1, the other glass formulas, slurry processing methods, sintering processes and testing methods are exactly the same.

[0081] The slurry described in this embodiment contains 68% copper powder, 15% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0082] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is less than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1 , the interface porosity is less than 5%, the edge thickness is 5.8μm, the resistance is 14mΩ / square, and the tension at the end is 16LB.

[0083] Example 9

[0084] Except for the proportion of inorganic additives in the slurry of this embodiment which is different from that of Embodiment 1, the other glass powder formula, slurry processing method, sintering process and testing method are exactly the same.

[0085] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 15% organic carrier, and 3% micron-sized eucryptite powder by mass percentage.

[0086] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is less than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1 , the interface porosity is less than 5%, the edge thickness is 7.2μm, the resistance is 13mΩ / square, and the tension at the end is 12LB.

[0087] Comparative Example 1

[0088] Except for the proportion of inorganic additives in the slurry of this embodiment which is different from that of Embodiment 1, the other glass powder formula, slurry processing method, sintering process and testing method are exactly the same.

[0089] The slurry described in this embodiment contains 75% copper powder, 8% glass powder, 17% organic carrier, and 0% micron-sized eucryptite powder by mass percentage.

[0090] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is less than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1, the interface porosity is less than 5%, the edge thickness is 3.0μm, the resistance is 12mΩ / square, and the tension at the end is 12LB.

[0091] Comparative Example 2

[0092] Except for the difference in the contents of glass powder and copper powder in the slurry of this embodiment from those of Embodiment 1, the other glass formulas, slurry processing methods, sintering processes and testing methods are exactly the same.

[0093] The slurry described in this embodiment contains 78% copper powder, 5% glass powder, 16% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0094] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is less than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1 , the interface porosity is 15%, the edge thickness is 3.8μm, the resistance is 25mΩ / square, and the tension at the end is 6LB.

[0095] Comparative Example 3

[0096] Except for the slurry formula of this embodiment which is different from that of Embodiment 1, other glass formulas, slurry processing methods, sintering processes and testing methods are exactly the same.

[0097] The slurry described in this embodiment contains 60% copper powder, 8% glass powder, 31% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0098] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is greater than 2.0%, which is similar to the bonding layer of the MLCC end face. Figure 1 , the interface porosity is 20%, the edge thickness is 1.8μm, the resistance is 200mΩ / square, and the tension at the end is 6LB.

[0099] Comparative Example 4

[0100] Except for the proportion of slurry carrier in this embodiment which is different from that in Embodiment 1, other aspects such as glass formula, slurry processing method, sintering process and testing method are exactly the same.

[0101] The slurry described in this embodiment contains 80% copper powder, 13% glass powder, 6% organic carrier, and 1% micron-sized eucryptite powder by mass percentage.

[0102] The viscosity change of the copper paste in this embodiment after one month of storage is shown in Table 2, and the change rate is greater than 25.0%. The viscosity is too high, and the MLCC is pulled out and cannot be sealed.

[0103] The glass formulas of Examples 1 to 6 above, the acid and alkali resistance weight loss rates of the glass powders, the hemispherical points of the glass powders, and the transition temperatures of the glass powders are shown in Table 1.

[0104] The viscosity of the slurry of Examples 1 to 8 and Comparative Examples 1 to 4 on the 1st day, the 15th day, and the 30th day, the thickness of the copper film after sintering, the thickness of the copper film around the edge of the MLCC, the resistivity of the end face, the end pull force, and the porosity of the interface are shown in Table 2. Table 1 Table 2

Claims

1. A glass powder for copper paste, characterized in that: The components are as follows by mass percentage: 18.0-28.0% SiO2, 25.0~35.0%B2O3, 30.0~45.0%BaO, 0~10%CaO, 0~5%Na2O, 0~8.0%TiO2, 0~6%CuO, 0~5.0%Sb2O3, 0~5.0%NaF.

2. The glass powder for copper paste according to claim 1, characterized in that: The glass powder has a transition temperature of 520-650°C, a hemispherical temperature of 650-800°C, a particle size of 1.5-2.5 microns, and an expansion coefficient of 6.5-9.5 ppm / °C.

3. A method for preparing the glass powder for copper paste according to claim 1-2, characterized in that: The preparation of the glass powder comprises the following steps: S1. Weigh glass raw materials, put them into a mortar and mix them for 10-15 minutes, then put them into a platinum crucible, melt them at 1250-1350°C for 40-90 minutes, and then pour the molten glass into a double-roll mill for quenching to make the molten glass into glass sheets. S2. Use a planetary ball mill to coarsely grind the glass flakes prepared in step S1 for 40-60 minutes and then sieve, and then finely grind for 70-120 minutes, dry and sieve to obtain glass powder for copper slurry. During the fine grinding process, water or alcohol is added as a ball grinding medium, and the mass ratio of water to glass powder is 1:1.

5.

4. A copper paste containing the glass powder according to claim 1, characterized in that: The invention is prepared by mixing 65.0-70% copper powder, 7-15% glass powder, 15.0-23.0% organic carrier, and 0-5% inorganic powder additive, etc., calculated by mass percentage. The organic carrier includes carrier A and carrier B.

5. The copper paste according to claim 4, characterized in that: The copper powder is a mixture of polygonal copper powder A and spherical copper powder B, wherein the average particle size of the spherical powder is 4-6 microns, the average particle size of the polygonal powder is 1.2-1.8 microns, and the weight ratio of the polygonal powder to the spherical powder is 1:(1-3).

6. The copper paste according to claim 4, characterized in that The slurry organic carrier comprises a solvent and a resin. The solvent comprises one or more of diethylene glycol butyl ether acetate, diethylene glycol butyl ether, dipropylene glycol butyl ether, and terpineol; the resin comprises one or two of ethyl cellulose and acrylic resin. The inorganic powder additive comprises one or two of fumed silica, cordierite, petalite powder, and eucryptite powder.

7. The method for preparing the slurry according to claim 4, comprising the following steps: S21, weighing the solvent and the resin, uniformly dissolving the resin in the solvent at 80-90° C., and fully stirring to form a uniform organic carrier. S22, the organic vehicle A, organic vehicle B, glass powder, copper powder A, and copper powder B prepared in step S are weighed in proportion and stirred to form a uniform slurry. The slurry is fully ground using a three-roll mill to finally prepare a copper slurry that meets the performance requirements.

8. The use of copper paste according to claims 6 and 7, characterized in that: The slurry end is attached to the end surface of the oxygen MLCC to form a terminal electrode, which is then dried and sintered in sequence to obtain a terminal electrode. The drying temperature is 120-130°C and the drying time is 10-20 minutes; The sintering process is as follows: first, in a wet nitrogen atmosphere, the temperature is increased to 500°C at a heating rate of 20-50°C / min and then kept at this temperature for 10 minutes; then, in a dry nitrogen atmosphere, the temperature is increased to 650-750°C at a heating rate of 30-50°C / min and then kept at this temperature for 10 minutes.

9. The use of copper paste according to claim 8, characterized in that: The copper terminal electrode is composed of a copper film and a substrate. There is no bulging, cracking, or glass overflow on the end surface. The average square resistance of the copper film is 4.5-15.3mΩ / square, and the tensile force of the terminal electrode is 10-15N.

10. The use of the glass powder according to claim 1, characterized in that: The application scenarios of this glass powder are not limited to copper paste, but can achieve high-strength interface bonding in the fields of gold paste, nickel paste, silver paste and ceramic sealing.

Citation Information

Patent Citations

  • Copper conductive slurry and preparation method thereof

    CN105225723A

  • Glass powder for high temperature-resistant aluminum slurry and preparation method thereof

    CN106746686A

  • Low-temperature glass powder, preparation method thereof and front electrode silver paste containing glass powder

    CN109180008A

  • Terminal electrode conductive copper paste and preparation method thereof

    CN114914012A

  • Glass powder and application of copper paste containing glass powder on ZnO voltage-sensitive ceramic substrate

    CN115611521A

Cited By

  • Heterogeneous metal oxide-coated copper-based powder and conductive copper paste, and methods of making and using the same

    CN122716202A